2017 IEEE International Conference on Smart Grid Communications (SmartGridComm) 2017
DOI: 10.1109/smartgridcomm.2017.8340703
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of storage under time varying electricity prices

Abstract: Abstract-End users equipped with storage may exploit time variations in electricity prices to earn profit by doing energy arbitrage, i.e., buying energy when it is cheap and selling it when it is expensive. We propose an algorithm to find an optimal solution of the energy arbitrage problem under given time varying electricity prices. Our algorithm is based on discretization of optimal Lagrange multipliers of a convex problem and has a structure in which the optimal control decisions are independent of past or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…Authors in [1] propose optimal energy arbitrage algorithm under time varying electricity prices. In this work it is shown that a time horizon of optimization can be subdivided into sub-horizons.…”
Section: Optimal Storage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in [1] propose optimal energy arbitrage algorithm under time varying electricity prices. In this work it is shown that a time horizon of optimization can be subdivided into sub-horizons.…”
Section: Optimal Storage Controlmentioning
confidence: 99%
“…In Section II we describe the cycle and calendar life of battery and list the typical values for power grid batteries. Section III summarizes the optimal arbitrage algorithm proposed in [1]. Section IV presents the mechanism to limit cycles of operation of a battery.…”
Section: Introductionmentioning
confidence: 99%
“…Most NEM policies indicate that consumers receive a rate at best equal to the buying price of electricity [4]. Authors in [5] consider storage operation under equal buy and sell price case. This framework is generalized in [6], covering cases where the ratio of buy and sell price could arbitrarily vary between 0 and 1.…”
Section: Introductionmentioning
confidence: 99%
“…This framework is generalized in [6], covering cases where the ratio of buy and sell price could arbitrarily vary between 0 and 1. For equal buying and selling price, the storage control becomes independent of inelastic load and renewable generation of the consumer [5], [7]. The cost function considered in this work includes inelastic load, renewable generation and storage charging and discharging efficiency, and ramping and capacity constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation